A high-fat high-sugar diet in adolescent rats impairs social memory and alters chemical markers characteristic of atypical neuroplasticity and parvalbumin interneuron depletion in the medial prefrontal cortex. Issue 4 (22nd March 2019) - Reichelt, Amy C.; Gibson, Gabrielle D.; Abbott, Kirsten N.; Hare, Dominic J.
Abstract : A hypercaloric diet given to adolescent rats induces social memory deficits and reduced neurochemical markers of normal social development. Abstract : Brain plasticity is a multifaceted process that is dependent on both neurons and extracellular matrix (ECM) structures, including perineuronal nets (PNNs). In the medial prefrontal cortex (mPFC) PNNs primarily surround fast-spiking parvalbumin (PV)-containing GABAergic interneurons and are central to regulation of neuroplasticity. In addition to the development of obesity, high-fat and high-sugar (HFHS) diets are also associated with alterations in brain plasticity and emotional behaviours in humans. To examine the underlying involvement of PNNs and cortical plasticity in the mPFC in diet-evoked social behaviour deficits (in this case social recognition), we exposed adolescent (postnatal days P28–P56) rats to a HFHS-supplemented diet. At P56 HFHS-fed animals and age-matched controls fed standard chow were euthanized and co-localization of PNNs with PV neurons in the prelimbic (PrL) and infralimbic (IL) and anterior cingulate (ACC) sub regions of the PFC were examined by dual fluorescence immunohistochemistry. ΔFosB expression was also assessed as a measure of chronic activity and behavioural addiction marker. Consumption of the HFHS diet reduced the number of PV+ neurons and PNNs in the infralimbic (IL) region of the mPFC by −21.9% and −16.5%, respectively. While PV+ neurons and PNNs were not significantly decreased in the ACC or PrL, the percentage of PV+ and PNN co-expressing neurons was increased in all assessed regions of the mPFC in HFHS-fed rats (+33.7% to +41.3%). This shows that the population of PV neurons remaining are those surrounded by PNNs, which may afford some protection against HFHS diet-induced mPFC-dysregulation. ΔFosB expression showed a 5–10-fold increase ( p < 0.001) in each mPFC region, supporting the hypothesis that a HFHS diet induces mPFC dysfunction and subsequent behavioural deficits. The data presented shows a potential neurophysiological mechanism and response to specific diet-evoked social recognition deficits as a result of hypercaloric intake in adolescence.